(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
A maximum bubble pressure method has been used to study dynamic surface tension, γ(t) of dibutylsulfoxide aqueous solutions at 0.0004-0.24 M concentration range. The γ(t) decays were measured in the range of 30 ms to 60 s and analyzed in term of asymptotic solutions to the Ward and Tordai equation. The adsorption model provided by diffusion was applied to describe the surface mass transfer process and to predict the dynamic surface tension.